The utility of diffusion-weighted imaging for differentiation of phyllodes tumor from fibroadenoma and breast cancer - Fang, Jinzhi; Zhang, Yuzhong; Li, Ruifeng; Liang, Lanlan; Yu, Juan; Hu, Ziqi; Zhou, Lingling; Liu, Renwei (Frontiers in Oncology, 2023)
Objective: To evaluate the utility of apparent diffusion coefficient (ADC) values for differentiating breast tumors. Methods: The medical records of 17 patients with phyllodes tumor (PT; circular regions of interest [ROI-cs] n=171), 74 patients with fibroadenomas (FAs; ROI-cs, n=94), and 57 patients with breast cancers (BCs; ROI-cs, n=104) confirmed by surgical pathology were retrospectively reviewed. Results: There were significant differences between PTs, FAs and BC in ADCmean, ADCmax, and ADCmin values. The cutoff ADCmean for differentiating PTs from FAs was 1.435×10-3 mm2/s, PTs from BC was 1.100×10-3 mm2/s, and FAs from BC was 0.925×10-3 mm2/s. There were significant differences between benign PTs, borderline PTs, and malignant PTs in ADCmean, ADCmax and ADCmin values. The cutoff ADCmean for differentiating benign PTs from borderline PTs was 1.215×10−3 mm2/s and borderline PTs from malignant PTs was 1.665×10−3 mm2/s. Conclusion: DWI provides quantitative information that can help distinguish breast tumors.